PENGARUH KREATIVITAS DAN MOTIVASI TERHADAP HASIL BELAJAR MATA PELAJARAN PRODUKTIF PEMASARAN PADA SISWA KELAS XI SMK NEGERI 2 TUBAN - Listiani, Ninis Mei (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The research is in order to know the effect of creativity and motivation toward the learners outcome of productive marketing on Grade XI SMK Negeri 2 Tuban. The data analysis technique is using partial and simultanous statistical technique of multiple linear tegression shich gives significant effect of learners outcome. The resultof this research shows that crativity variabel and motivation gives effect on the learners outcome as 88,5% while the resst is effected by other variabel which doesnt use in this research